Blood pressure lowering, antidyslipidemic and nitric oxide modulatory effects of methanol extract of struchium sparganophora leaves on dexamethasone-salt model of hypertension in rats. Issue 1 (1st January 2021) - Adeosun, Abiola M.; Aroworamimo, Abdulrahman D.; Ighodaro, Osasenaga M.; Asejeje, Folake O; Akinloye, Oluseyi A.
ABSTRACT: The use of glucocorticoids causes elevation of blood pressure (BP) in man and experimental rats. We evaluated the antihypertensive potential of methanol leaf extract of Struchium sparganophora  (SPA) on dexamethasone-salt-induced hypertension in  rats . Rats were assigned randomly to six groups (n=4/group). Group A represented control, while BP elevation (BP≥140/90) was induced in groups B-F via single subcutaneous administration of dexamethasone at a dose of 2 mg/kg with 4% NaCl substituted as drinking water for 5 days. Groups B was left untreated and treatments of other groups twice daily (C-F) for 10 days were as follows: C: nifedipine 3 mg/kg D: nifedipine 3 mg/kg + SPA l300 mg/kg, E: SPA 300 mg/kg and F: SPA 600 mg/kg. BP was read using a noninvasive method, lipid profile and nitric oxide (NO) concentration were determined with appropriate procedures. SPA at 300 and 600 mg/kg markedly decreased the systolic and diastolic BP below suboptimal value of 140/90. Treatment with SPA caused increase (P<0.05) in the levels of HDL-cholesterol and NO as well as concomitant decrease in triglyceride concentration. This study revealed that SPA might lower blood pressure by increasing NO concentration and maintaining lipid homeostasis in hypertensive rats. Graphical abstract: uf0001